Insulin-like growth factor 2 receptor is a key immune-related gene that is correlated with a poor prognosis in patients with triple-negative breast cancer: A bioinformatics analysis - Zhong, Ying; Ren, Xinyu; Cao, Xi; Xu, Yali; Song, Yu; Zhou, Yidong; Mao, Feng; Shen, Songjie; Wang, Zhe; Sun, Qiang (Frontiers in Oncology, 2022)
Background: Immunotherapy plays an important role in the treatment of triple-negative breast cancer (TNBC). This study aimed to identify immune-related genes that are associated with the prognosis of TNBC patients as possible targets of immunotherapy, alongside their related tumor-infiltrating lymphocytes (TILs). Methods: The clinical data and gene expression profiles of patients with breast cancer were extracted from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases and divided into training (n=1053) and verification (n=508) groups. CIBERSORT was used to predict the differences in immune cell infiltration in patient subsets that were stratified according to risk. Gene Ontology (GO) enrichment analysis was used to identify pathways associated with immune-related genes in patient subsets that were stratified according to risk. The clinical data and insulin-like growth factor 2 receptor (IGF2R) expression profiles of patients with breast cancer were extracted from METABRIC. The expression of IGF2R and TILs were evaluated in a cohort containing 282 untreated patients with TNBC. The correlations of IGF2R expression, TILs, and clinicopathological parameters with patient prognosis were analyzed in the whole cohort. Results: The prognostic model, which was composed of 26 immune-related gene pairs, significantly distinguished between high- and low-risk patients. Univariate and multivariate analyses indicated that the model was an independent prognostic factor for breast cancer. Among the identified genes, the expression of IGF2R significantly distinguished between high- and low-risk patients in The Cancer Genome Atlas (P=0.008) and in METABRIC patients (P<0.001). The expression of IGF2R was significantly associated with clinical risk factors such as TNBC, estrogen receptor (ER)-negative expression, human epidermal growth factor receptor 2 (HER2)-positive expression, and age ≤60 years old in METABRIC patients. In addition, the patients with IGF2R-positive expression had lower disease-free survival (DFS) rates than those with IGF2R-negative expression in the TNBC cohort (67.8% vs. 78.5%, P=0.023). IGF2R expression also was significantly negatively correlated with TILs, particularly with CD8+ TILs and CD19+ TILs in the cohort of patients with TNBC. Conclusion: IGF2R can be used as an indicator of a poor prognosis in TNBC patients and as a potential target and research direction for TNBC immunotherapy in the future.